Atypical blastomycosis in a pregnant woman - Corey M. DeWitt, MD; Katelyn Shea, MD; Laura A. Greene, MD; Joseph C. Pierson, MD (Wolters Kluwer, 2019)
Blastomycosis is a rare fungal infection that frequently involves the skin. Atypical presentations are important to identify, especially in pregnant patients, to initiate appropriate therapy and prevent complications. Uniquely, we describe a case of atypical blastomycosis that presented with painful cutaneous abscesses in a pregnant patient, with dissemination to the central nervous system. The case was successfully treated with liposomal amphotericin B transitioned to voriconazole after delivery without complications for the patient or fetus. Keywords: Blastomycosis, pregnancy, amphotericin B